(untitled) (Journal of the College of Basic Education, 2024)
The deconstructive approach is one of the directions of reception and reading theories, but its emergence was not a coincidence. Rather, it had prior foundations and roots at the hands of some philosophers and critics such as Martin Heidegger, Michel Foucault, Martin Hegel, Edmund Husserl and others, but it was associated with the name of Jacques Derrida because he was the most prominent person who looked at it and specialized in it in his clear concept of deconstruction and its more specific meaning, in terms of classifying and writing books (writing). And the difference) and (the science of writing) and ot The most important foundations and concepts on which the method was founded are deferred difference, criticism of centralization, deconstructive reading, presence and absence. As for influence, the deconstructive method was influenced and emerged from structuralism or is a response to it, because it adopted the fixed center and rejected pluralism. The deconstructive approach adopted the idea of ​​writing and considered it to be the origin and precedent of sound or speech. As for the signification, it was replaced by the effect according to the duality of the signifier and the signified, because it believed in the effect and the multiplicity of meanings if it considered them infinite, and it transformed the language from the concept of signs to the concept of the effect as the bearer of the qualities of writing. hers.